Default risk in Microfinance Institutions: Case study of a Costa Rican company - Barboza-Navarro, David (2023)
The most recent Economic Report of the Inter-American Development Bank ranks Costa Rica as the second country in Central America with the highest household indebtedness, and almost half of households have no savings. These conditions have led to increases in the default rates of loan creditors. This research analyzes the factors affecting default in a Costa Rican Microfinance Institution that grants microcredits to individuals and small businesses without access to traditional bank financing. An econometric approach with panel data was applied and the results show that default is affected by autoregressive components and the financed activity. The application of these methodologies allows strengthening credit analysis and the selection of market niches to mitigate the default risk.